Red and blue wavelengths affect the morphology, energy use efficiency and nutritional content of lettuce (Lactuca sativa L.) - Xiao-li Chen (Nature Portfolio, 2021)
Abstract Since red (R) and blue (B) LED light has different quantum efficiency and photoelectric conversion efficiency, mixed RB with different proportions of R and B results in varied energy consumption. In order to improve the energy use efficiency of the closed-type plant production systems, the effects of R and B proportions on the electric use efficiency (EUE), light use efficiency (LUE) as well as the quality of butter leaf lettuce were evaluated in this study. Lettuce seedlings were cultivated in a plant factory with artificial lighting (PFAL) and subjected to eleven combinations of R and B (100%R, 90%R, 80%R, 70%R, 60%R, 50%R, 40%R, 30%R, 20%R, 10%R, 0%R; the rest of the photons in each treatment were B) with the same total photosynthetic photon flux density (PPFD) and photoperiod (200 ± 3 μmol·m−2·s−1, 16 h) for 35 days. The results showed that palpable petiole distortion appeared when R proportion was more than 70% and the distortion was aggravated with the increase of R proportion. The highest EUE and LUE were both detected in lettuce under 90%R treatment, which were respectively 3.64% and 1.20%. The least number of photons and the least electricity amount required to produce 1 g dry weight of lettuce was respectively 2.92 mol and 1.67 MJ, which were both detected in lettuce treated with 90%R. The sucrose content in lettuce treated with more than 50%R was significantly higher than those treated with less than 50%R (50%R included). Lettuce treated with 80%R possessed the highest soluble sugar content as well as the lowest crude fiber and nitrate content (not significantly different with the minimum values). R proportion exceeding 50% in mixed RB light was beneficial to the accumulation of hexose and sucrose, as well as the decomposition of nitrate in lettuce. The vitamin C content in lettuce treated with 100%R was significantly higher than that in lettuce under other treatments in the study. On the whole, the study indicated that the proportions of R and B affected the energy use efficiency and quality of lettuce in closed plant factory, however the responses of plants to the proportions of R and B varied according to different indexes. Thus, some indexes of top priority should be determined before choosing the optimal proportions of R and B.